First Report of Powdery Mildew on Quercus rubra in Germany - Muhammad Saeed; Sakshi Sharma; Stefan Seegmüller; Matthias Hah (한국균학회지)
Oak powdery mildew (OPM) is a major disease of oak trees native in central Europe. In contrast, red oak (Quercus rubra) is generally considered immune to OPM. In 2024, five instances of powdery mildew infection were observed on Q. rubra in Kaiserslautern, Germany. Molecular analyses identified the pathogens as either Erysiphe alphitoides or E. quercicola. Controlled inoculations of Q. rubra leaves with E. alphitoides inoculum obtained from Q. rubra showed very limited pathogen development. Few germinated conidia formed secondary hyphae with haustoria, and no mycelium was observed, suggesting nonhost resistance to OPM. While Q. rubra appears resistant to OPM, these sporadic reports suggest continuous monitoring to better understand this potential disease threat for an important tree species.